Происхождение удмуртского народа: [монография] / М. Г. Атаманов-Эграпи - Атаманов-Эграпи Михаил Гаврилович (Удмуртия, 2017)
Экземпляры: Ф. 4 (20210503) / Инвентарный номер: 48197 / Цена: 500.00 / Сис.шифр: 63.529(2Рос.Удм) / Авт.знак: А 92 / ГРНТИ: 03.61.91 / ББК: 63.529(2Рос.Удм)